Green Human Resources Management in Waste Management (Study Southeast Asia) - Fanesha Fazriyani; Ali Imron; Evan Lau (TIJAB (The International Journal of Applied Business), 2025)
Background: Waste management challenges numerous countries, particularly developing ones. This review indicates that Southeast Asia, particularly Vietnam, receives a score of 24.5 points, considered low. Objective: This study reviews the literature on green human resource management in waste management. The author examines the issue from a regional perspective, particularly emphasizing Southeast Asia. Method: This bibliometric analysis is based on data compiled over the last five years, from 2020 to 2024. Results: In Southeast Asia, the company can effectively manage pollution by utilizing green human resources, including employees' skills, knowledge, and abilities related to environmental initiatives or practices. In Vietnam, initiatives are underway to promote the advancement of environmentally beneficial technologies. They are constructing a Vietnam green technology database based on an annual green technology classification system: establishing a specialized organization to develop ecologically friendly technology similar to China's green bank. By implementing green human resource management practices, organizations in Indonesia foster a work environment in which employees are confident and prepared to contribute to environmentally favourable initiatives. Conclusion: Singapore has the highest score for Southeast Asia's most environmentally friendly country. Malaysia and Indonesia affirm that employees with skills, knowledge, and abilities related to environmental initiatives or practices are more likely to engage in environmentally oriented behaviour. Kamboja actively encourages employees to develop environmentally friendly ideas; knowledge transfer is required to achieve a better Environmental Performance Index. Keywords: Green Human Resource Management, Waste Management, Environmental Performance